Isolation and preliminary characterization of temperature-sensitive mutants of measles virus. - Haspel, M V (1975)
Twenty-four genetically stable temperature-sensitive mutants of measles virus were isolated after mutangenesis by 5-azacytidine, 5 fluorouracil, or proflavine. The restricted replication of all mutants at 39 C was blocked subsequent to cell penetration and could not be attributed to heat inactivation of virus infectivity. Complementation analysis was made possible through the use of poly-L-ornithine. The members of one complementation group exhibited wild-type RNA synthesis at the nonpermissive temperature and induced the synthesis of virus antigens. These mutants were found defective in both hemolysin antigen synthesis and cell fusion "from within," supporting the unitary hypothesis for these functions. The members of the other two complementation groups synthesized neither virion RNA nor detectable virus antigens at the nonpermissive temperature.